Philippines : Invigorating Growth, Enhancing Its Impact - World Bank (Washington, DC, 2012)
Major fiscal adjustment during 2005-06, aided by abundant global liquidity, has turned around market sentiment on the Philippines. Stocks, the peso and reserves have all risen significantly, as have foreign direct investment and portfolio inflows, while interest costs and spreads for government borrowing have fallen along with inflation. Real GDP grew by 5.4 percent in 2006 and real GNP by 6.2 percent, marking the first time that three consecutive years of growth of 5 or more percent was recorded since the 1970s. Strong growth in business process outsourcing, electronics exports and remittance-driven consumption served as important props for higher growth. This paper includes the following headings: recent economic developments; how robust is present growth; invigorating growth, enhancing its impact; and maximizing the benefits of growth for the poor.